Mechanics of surface crosslinked poly(dimethyl siloxane) microstructure used for microcontact transfer printing. Issue 31 (13th April 2017) - Bao, Chao; Wang, Zhifan; Liu, Yu; Zhang, Yanning; Nie, Heng‐Yong; Lau, Woon‐Ming; Mei, Jun
ABSTRACT: In microcontact transfer printing, the mechanics of the microstructure on an elastomeric stamp are crucial for obtaining a printed image with high feature resolution and repeatability. In this article, we are dedicating research efforts to visit a methodology for surface crosslinking a poly(dimethyl siloxane) microstructure, implemented by a hyperthermal hydrogen‐induced crosslinking technique. The significant enhancement of Young's modulus of elastomeric base after the surface crosslinking is confirmed by consequent ab initio calculation and numerical simulation. Experiments based on compression test and forced lateral scanning have been done for verifying the enhanced mechanic stability. This work provides a surface treatment way for fabricating a printing stamp with high robustness and transfer printing quality. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45166. Abstract :